Writing program architecture: thirty cases for reference and research - Finer, Bryna Siegel, editor; White-Farnham, Jamie, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Information and analysis concerning the material, logistical, and rhetorical features of a writing program, such as contracts, funding lines, and curriculum. Drawing from award-winning programs, the contributors analyze reporting lines, funding sources, jurisdiction of the writing program administrator (WPA), available majors, and other critical programmatic matters.--Provided by publisher.
Writing program architecture: an introduction with alternative tables of contents / Jamie White-Farnham and Bryna Siegel Finer -- Miami University major in professional writing / Heidi A. Mckee -- Oakland University writing and rhetoric major / Greg A. Giberson, Lori Ostergaard, and Marshall Kitchens -- Purdue University Graduate Program in rhetoric and composition / Patricia Sullivan -- Rowan University major in writing arts / Sanford tweedie -- University Of Rhode Island writing major / Nedra Reynolds and Joannah Portman-Daley -- University of Wyoming professional writing minor / Michael Knievel and Meg Van Baalen-Wood -- Louisiana State University Communication across the Curriculum / Sarah Liggett -- Monmouth College Communication across the Curriculum / Bridget Draxler -- Old Dominion University Quality Enhancement Plan (QEP) / Remica Bingham-Risher -- University of Missouri Campus Writing Program / Bonnie Selting and Amy Lannin -- Arizona State University Writers' Studio Online / Angela Clark-Oates -- John Jay College Of Criminal Justice first year writing program / Tim McCormack and Mark McBeth -- Onondaga Community College Writing Program / Malkiel Choseed -- Our Lady of the Lake University QUEST first-year writing program / Candace Zepeda -- St. Louis Community College ESL program / Lisa Wilkinson and Heather McKay -- University of Notre Dame University Writing Program / Patrick Clauss -- University of Wisconsin/Eau Claire University Writing Program / Shevaun Watson -- University of Wisconsin/Superior Basic Writing / John McCormick, Heather McGrew, and Jamie White-Farnham -- Utah Valley University Department Of Basic Composition / Jacqueline Preston and Deborah Marrott -- Duquesne University Writing Center / James P. Purdy -- Indiana University Of Pennsylvania Kathleen Jones White Writing Center / Leigh Ann Dunning and Ben Rafoth -- University of Connecticut Writing Center / Thomas Deans and Kathleen Tonry -- Shepherd University Academic Support Center / Christy I. Wenger -- Wallace Community College Center For Writing And Writing Instruction / Emily W. Cosgrove -- Westminster College Writing Center / Christopher LeCluyse -- Arizona State University writing programs in the Department of English / Shirley K. Rose, Susan Naomi Bernstein, and Brent Chappelow -- Colby College Writing Program & Farnham Writers' Center / Stacey Sheriff and Paula Harrington -- Drew University Vertical Writing Program / Sandra Jamieson -- New Mexico Tech Writing Program And Writing Center / Maggie Griffin Taylor, Julianne Newmark, and Steve Simpson -- Pomona College WAC-based First-Year Writing Seminar And Writing Center / Dara Regaignon.
Keywords: Writing centers -- United States -- Administration -- Case studies; English language -- Rhetoric -- Study and teaching (Higher) -- United States